2008
DOI: 10.1063/1.2954037
|View full text |Cite
|
Sign up to set email alerts
|

Drying of salt solutions in porous materials: Intermediate-time dynamics and efflorescence

Abstract: Drying of salt solutions leads to the accumulation of salt at any surface where evaporation occurs. When this drying occurs within porous media, the precipitation of salts or efflorescence is generally to be avoided. A one-dimensional model for the drying processes in initially saturated porous materials was presented by Huinink et al. ͓Phys. Fluids 14, 1389 ͑2002͔͒ and analytical results were obtained for short times when the concentration distribution evolves diffusively. Here, we present analytical results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 13 publications
6
67
0
Order By: Relevance
“…The equation for convective-diffusive salt transport in porous media can be written in dimensionless form as [12,16]:…”
Section: Salt Crust Formation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equation for convective-diffusive salt transport in porous media can be written in dimensionless form as [12,16]:…”
Section: Salt Crust Formation Conditionsmentioning
confidence: 99%
“…Recent studies have addressed crystal growth in pores and ensuing damage [3,9,28,[31][32][33], the mechanisms of efflorescence and subflorescence, as well as their emergence as part of transport/evaporation processes [8,12,18,24,29,35,38]. However, the formation and physical properties of salt crusts remain poorly known, primarily due to their thin and fragile characteristics that challenge laboratory experiments [29].…”
Section: Introductionmentioning
confidence: 98%
“…As water evaporates from cement, the solute concentration near the drying surface increases, so the solute tends to diffuse toward the interior. Guglielmini et al (2008) have shown that the solute concentration at the drying surface, c, rises with time, t, during the constant rate period according to…”
Section: Transport Kineticsmentioning
confidence: 99%
“…The dynamic equilibrium between evaporative flux (drying) and advective supply of solution to the evaporation front dictates the transition height from efflorescence to subflorescence ( Fig. 3a and b) [7,13,45,47].…”
Section: Capillary Risementioning
confidence: 99%